EFEKTIVITAS DAN PENGARUH PNPM MANDIRI PERDESAAN, ALOKASI DANA DESA, PENDAPATAN ASLI DESA DAN JUMLAH PENDUDUK TERHADAP JUMLAH KEPALA KELUARGA MISKIN DI KABUPATEN KEBUMEN TAHUN 2009-2011 - Prihartini Budi Astuti (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2014)
The problem of poverty is a complex and multidimensional problem, therefore poverty reduction efforts have to be comprehensive, covering various aspects of society and implemented in an integrated manner. The problem of poverty in Indonesia can’t be separated from the context of the institutional and governance. After about six years since the implementation of regional autonomy, a number of challenges remain, but the process of decentralization has the potential to further improve welfare by bringing services closer to the people of Indonesia, and especially to the poor. Poverty reduction efforts in the process of being local, and regional government has now followed in the preparation of national poverty reduction strategies. This study aims to determine the effectiveness and influence of PNPM Rural Women's Savings and Loans (SPP), PNPM Rural Non-SPP, the Village Fund Allocation (ADD), Village Revenue (pads) and the number of residents to the number of poor families in Kebumen Regency in 2009-2011 either partially or simultaneously. The results of data analysis showed that the variables PNPM Rural Women's Savings and Loans (SPP) has a positive and significant impact on the number of poor families with a coefficient of 0.005459, PNPM Rural Non-SPP negative but not significant effect on the number of poor families with coefficient of -0.002676, Village Fund Allocation (ADD) and significant negative effect on the number of poor families with a coefficient of -0.010433, Revenue Village (PADs) has a significant negative effect on the number of poor families with a coefficient of -0, while Population variable can negatively but not significantly influence to the number of poor families with a coefficient of -0.017860. From the results of this analysis, it is concluded that the PNPM Rural Women's Savings and Loans (SPP), PNPM Rural Non-SPP, the Village Fund Allocation (ADD), and Revenue Villages (PADS) is effective in reducing poverty in Kebumen Regency in the year of 2009 to 2011, because in general there has been a successful program, the successful achievement of goals and overall objectives. Keywords: number of poor families, PNPM Rural, Village Fund Allocation, Revenue Villages